P073 High LDL levels lessen bone destruction during antigen-induced arthritis by inhibiting osteoclast formation and function. (March 2019) - van den Bosch, MH; Ascone, G; Di Ceglie, I; Walgreen, B; Sloetjes, AW; Lindhout, E; Bot, I; van de Loo, FA; Koenders, MI; van der Kraan, PM; Blom, AB; van Lent, PL
Abstract : Career situation of first and presenting author: Post-doctoral fellow. Introduction: Rheumatoid arthritis (RA) is a chronic inflammatory disease, characterized by severe joint inflammation and bone destruction as the result of increased numbers and activity of osteoclasts. In RA, joint destruction is associated with high levels of low-density lipoprotein (LDL), which in inflammatory environments is oxidized into oxLDL. However, the effects of high (ox)LDL levels on the differentiation and activation of osteoclasts remains elusive. Objectives: Here, we investigated the effects of high LDL and oxLDL levels on osteoclast differentiation. Methods: Antigen-induced arthritis (AIA) was induced in Apoe -/- mice that spontaneously develop high LDL levels. Bone erosion was assessed with histology and numbers of osteoclasts were determined with staining for tartrate-resistant acid phosphatase (TRAP). Numbers of CD11b + /Ly6C high and CD11b - /Ly6C high osteoclast precursors were determined by flow cytometry. In vitro osteoclast differentiation from bone marrow cells was induced with macrophage colony-stimulating factor (M-CSF) and receptor activator of nuclear factor kappa-B (RANK) for 7 days. Gene expression was determined with qPCR. Results: Whereas basal levels of bone resorption were comparable between WT and Apoe -/- mice, induction of AIA resulted in significantly lower bone resorption in Apoe -/- mice as compared to WT mice, which was associated with lower number of TRAP + osteoclasts along the bone surface. However, the absence of Apoe did not result in altered numbers of osteoclast precursors in the bone marrow of naïve mice, whereas even increased numbers were observed in Apoe -/- mice during AIA. Moreover, in vitro osteoclastogenesis showed comparable numbers and mRNA expression of osteoclast markers, such as c-Fms, RANK, NFATc1, DC-STAMP, TRAP, CTR, ClC-7, CA-II, Cat K and MMP-9. Addition of oxLDL, but not LDL, to pre-osteoclasts from day 3 and mature osteoclasts from day 6 of osteoclastogenesis strongly reduced the number of TRAP + osteoclasts and their resorptive capacity. This was accompanied by a decreased expression of various osteoclast markers. Interestingly, oxLDL decreased the expression of osteoclast -associated receptor ( Oscar ) and the DNAX adaptor protein-12 encoding gene Tyrobp, which regulate the immunoreceptor tyrosine-based activation motif (ITAM) mediated co-stimulation signaling pathway that is strongly involved in osteoclastogenesis. Conclusions: Apoe -/- mice have decreased bone resorption during experimental RA, probably via oxLDL-mediated interference in the co-stimulatory pathway during osteoclastogenesis. Disclosure of Interest: None declared.